Overview of Nurses Perception about Caring Based on Technology in the ICU and ER of Jember Region Hospital - Nur Rohmawati; Anisah Ardiana; Kholid Rosyidi Muhammad Nur (Nursing and Health Sciences Journal (NHSJ), 2021)
Caring in acute and critical care rooms has a more complex and dynamic nature due to unstable patient conditions and requires more attention from nurses. Nurses' technological competence represents their caring based on nursing science practice. This study aimed to find out how nurses’perception of caring based on technology in the Intensive Care Unit and Emergency Room in Jember Region. This study used a quantitative method based on a descriptive survey. This study used a total sampling, with a total of 47 nurses as respondents. The researcher used a demographic questionnaire and modification of caring attribute, professional self-concept, and technological influence scale to collect data. In this study, univariate analysis was applied to analyze the data. The median score was 68, as the scores approach the maximum score of 76. This study demonstrates that nurses have a good perception toward caring based on technology. The conclusion on this study is nurses perception of caring based on technology are generally positive. To further improve nurses' perceptions of caring expressed through technological competence, the researcher advises the managerial department to facilitate education and training on technological competence in order to provide better care and caring to patients. Keywords: Caring Based on Technology; Nurses; Perception